Cybercrime And Organized Crime in a Specialized Unit of the Public Prosecutor's Office in the Ancash Region -2024 - Rodríguez Silva, Williams Marino (2024)
This research aimed to determine the relationship between cybercrime and organized crime in a specialized unit of the public ministry of the Ancash - 2024 region. A methodology with a quantitative approach, of a basic type, non-correlational design and transversal scope was used in a sample of 35 prosecutors. To whom two questionnaires of closed questions with answers of the Likert scale type were administered; the first questionnaire of 20 items with reliability of α1 = 0.935; and the second questionnaire, of 20 items with reliability of α2 = 0.922. The results showed a high level of cybercrime with 48.6% and a medium perception of organized crime with 48.6%, presenting as a conclusion: a significant relationship was determined (Rho = 0.837; sig. = 0.000 < 0.05) between cybercrime and organized crime in a specialized unit of the public ministry of the Ancash region, referring that cybercrime and organized crime in the digital age are enhanced by interrelated factors that act as facilitators, these factors contribute to creating an environment of difficult regulation and surveillance.